2015
DOI: 10.1371/journal.pone.0115736
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cathepsin and Furin Proteolytic Enzymes Involved in Viral Fusion Protein Activation in Cells of the Bat Reservoir Host

Abstract: Bats of different species play a major role in the emergence and transmission of highly pathogenic viruses including Ebola virus, SARS-like coronavirus and the henipaviruses. These viruses require proteolytic activation of surface envelope glycoproteins needed for entry, and cellular cathepsins have been shown to be involved in proteolysis of glycoproteins from these distinct virus families. Very little is currently known about the available proteases in bats. To determine whether the utilization of cathepsins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 103 publications
1
19
0
Order By: Relevance
“…lung) cells [ 64 ] that have a furin enzyme with ∼90% sequence homology to bats in the Rhinolopus family. Our previous studies on paramyxovirus virus fusion protein cleavage have shown that efficient furin and cathepsin cleavage occurs in these cells, although the furin cleavage occurs with delayed kinetics compared to Vero or A549 cells [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…lung) cells [ 64 ] that have a furin enzyme with ∼90% sequence homology to bats in the Rhinolopus family. Our previous studies on paramyxovirus virus fusion protein cleavage have shown that efficient furin and cathepsin cleavage occurs in these cells, although the furin cleavage occurs with delayed kinetics compared to Vero or A549 cells [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…lung) cells [ 64 ] that have a furin enzyme with ~90% sequence homology to bats in the Rhinolopus family. Our previous studies on paramyxovirus virus fusion protein cleavage have shown that efficient furin and cathepsin cleavage occurs in these cells, although the furin cleavage occurs with delayed kinetics compared to Veros or A549s [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…1b ). Previous work has shown that the fusion proteins of Hendra virus, processed by cathepsins, and parainfluenza virus 5, processed by furin, are also cleaved in P. alecto cells [ 65 ]. Pulse-chase analysis in this prior study demonstrated an increase in processing kinetics, although this kinetic difference can be accounted for by differences in protease expression levels between different bat cell lines (pt.…”
Section: Discussionmentioning
confidence: 99%
“…Furin is ubiquitously expressed at different levels in all tissues 2,3 . However, kinetics of furin-like enzyme activity are different among species – e. g. human lung cells display quicker kinetic than fruit bat (Pteropus alecto ) lung cells 4 – and may not fully explain SARS-CoV-2 enhanced infectivity. On the other hand, we detected several unique amino acid residues that distinguish the spike (S) glycoprotein from ancestral bat and pangolin strains, tested for selective pressure acting on these residues, and further performed homology modeling and molecular dynamic simulations to understand the impact of the cleavage site on the S glycoprotein structure, as it might be modulating infectivity and pathogenicity of the virus 7 .…”
Section: Mainmentioning
confidence: 99%